Penerapan Metode Probing Prompting Untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Mahasiswa AMIK Mitra Gama : Application of the Probing Prompting Method To improve Mathematics Learning Activities and Learning Outcomes at Amik Mitra Gama - Novidawaty Tambunan (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2020)
In attending mathematics lectures, new students are often passive due to the non-uniform background of understanding concepts and adjustment factors for the new campus environment. This research is a Classroom Action Research (CAR) that aims to determine the increase in activity and learning outcomes of Discrete Mathematics in the first semester students of the Computer Management Skills Program to apply the Probing Prompting learning method. The research was conducted on 2018/2019 odd semester students with a total of 30 students. Data were collected through observation and learning outcomes tests. The application of the probing prompting method on the subject of the Matrix can increase the learning activities of new students; it can be seen that the average value of student learning activities from cycle I to cycle II has increased significantly. Student mathematics learning outcomes on the Matrix subject also experienced a significant increase from cycle I to cycle II. It can be concluded that the use of the probing prompting learning model in mathematics learning in the Matrix subject can increase student activity and learning outcomes.